Characterization of CYP154F1 from Thermobifida fusca YX and Extension of Its Substrate Spectrum by Site‐Directed Mutagenesis. (26th January 2018) - Rühlmann, Ansgar; Groth, Georg; Urlacher, Vlada B.
Abstract: Previous studies on cytochrome P450 monooxygenases (CYP) from family 154 reported their substrate promiscuity and high activity. Hence, herein, the uncharacterized family member CYP154F1 is described. Screening of more than 100 organic compounds revealed that CYP154F1 preferably accepts small linear molecules with a carbon chain length of 8–10 atoms. In contrast to thoroughly characterized CYP154E1, CYP154F1 has a much narrower substrate spectrum and lower activity. A structural alignment of homology models of CYP154F1 and CYP154E1 revealed few differences in the active sites of both family members. By gradual mutagenesis of the CYP154F1 active site towards those of CYP154E1, a key residue accounting for the different activities of both enzymes was identified at position 234. Substitution of T234 for large hydrophobic amino acids led to up to tenfold higher conversion rates of small substrates, such as geraniol. Replacement of T234 by small hydrophobic amino acids, valine or alanine, resulted in mutants with extended substrate spectra. These mutants are able to convert some of the larger substrates of CYP154E1, such as ( E )‐stilbene and (+)‐nootkatone. Abstract : Scope determination : Key residues accounting for different activities of CYP154F1 and its thoroughly characterized relative CYP154F1 were identified based on a structural alignment of their homology models. Subsequently, site‐directed mutagenesis was applied to extend the substrate spectrum of CYP154F1 and increase its activity.